2017
DOI: 10.1080/14616734.2017.1398764
|View full text |Cite
|
Sign up to set email alerts
|

Parental reflective functioning and executive functioning in mothers with substance use disorder

Abstract: Having a substance use disorder (SUD) may adversely affect caregiving capacities. Reflective functioning (RF) and executive functioning (EF) are both important capacities for sensitive parenting, and are often impaired in a SUD. Only a few studies have explored the possible association between the two phenomena. In this study, we used a neuropsychological test battery to assess EF, and the Parent Development Interview to assess RF in a sample of mothers with a SUD (N = 43). Although parental RF (PRF) was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 140 publications
(152 reference statements)
8
34
1
2
Order By: Relevance
“…Contrary to the results in our study, previous research has found that EF impairments are associated with experience and management of general life stress (Hofmann et al, ; Koenig, Walker, Romeo, & Lupien, ; Schmeichel & Tang, ; Williams et al, ). Further, EF has been found to be associated with PRF in mothers with SUD (Håkansson et al, ; Rutherford et al, ; Yatziv et al, 2018), and we suggest that EF capacities and deficits might affect relational forms of stress (parental stress and psychological distress) and particularly in mothers with SUD because of a possible mediating functioning of PRF. Indeed, these associations between EF and general life stress may not be present as general life stress is less relationally focused compared with parental stress and psychological distress.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Contrary to the results in our study, previous research has found that EF impairments are associated with experience and management of general life stress (Hofmann et al, ; Koenig, Walker, Romeo, & Lupien, ; Schmeichel & Tang, ; Williams et al, ). Further, EF has been found to be associated with PRF in mothers with SUD (Håkansson et al, ; Rutherford et al, ; Yatziv et al, 2018), and we suggest that EF capacities and deficits might affect relational forms of stress (parental stress and psychological distress) and particularly in mothers with SUD because of a possible mediating functioning of PRF. Indeed, these associations between EF and general life stress may not be present as general life stress is less relationally focused compared with parental stress and psychological distress.…”
Section: Discussionsupporting
confidence: 52%
“…Prefrontal brain areas that are important for EF are areas also found to be involved with PRF (Abu‐Akel & Shamay‐Tsoory, ; Oldrati, Patricelli, Colombo, & Antonietti, ), which suggests a possible association between EF and PRF. Furthermore, mothers with SUD who have negative to low PRF have been found to exhibit weaker EF compared with mothers with adequate PRF (Håkansson et al, ). Low mentalizing capacities have been associated with elevated stress levels (Luyten, Fonagy, & Lowyck, ), whereas adequate PRF is associated with increased tolerance of child distress (Rutherford, Goldberg, Luyten, Bridgett, & Mayes, ).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, there were no significant differences between mothers with low and adequate PRF in regards of what type of substance they preferred. Furthermore, mothers with adequate PRF performed according to norms in diverse executive functions (EF), while mothers with negative to low PRF had multiple deficits in EF (Håkansson et al, 2017). This association between PRF and EF was also highlighted in a recent study on mothers from a normal population (Rutherford et al, 2017).…”
Section: Introductionmentioning
confidence: 87%
“…The experience of epistemic mistrust in relational settings may be particularly high in vulnerable populations, which includes mothers with SUD. Indeed, mothers with SUD have been identified to have a low PRF (Håkansson, Söderström, Watten, Skårderud, & Øie, 2017;Levy & Truman, 2002;Pajulo et al, 2012;Suchman, DeCoste, Castiglioni, Legow, & Mayes, 2008). In a previous study, we separated SUD mothers according to their PRF level, which was either negative to low or adequate to high (Håkansson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation